DETAIL STUDY OF MAHA SHANKHA VATI - A LITERARY REVIEW - R. Hedaoo, Nalini; B. Bandale, Mukund; Patil, D.V.; Biradar, V. A. (International Journal of Ayurveda and Pharma Research, 2016)
In Ayurveda Classics Sankha Vati seems with two names Sankha Vati and Maha Shankha Vati.  Both these preparations are selected for the present study are comes under Khalveeya Rasa Kalpana & Sagandha and Niragni Moorchhana preparation. This study having the aim of detailed literary study of Maha Sankha Vati & Sankha Vati. In Ayurveda classics Four different references of MahaSankha vati & ten references of Sankha Vati found. In Ayurveda Formulary of India Maha Shankha Vati is prescribed from Bhaishjya Ratnavali, but this reference actually originated from Rasendra Chintamani. After considering various reference in text, it was found that fourteen drugs are common according to all the references, these are Parada, Gandhaka, Vatsanabha, Shankha Bhasma, Hingu, Chincha Kshara, Panchalavana, Maricha, Pippali & Sunthi. In Bharat Bhaishajya Ratnakar mentioned that, if Loha & Vanga added in Sankha Vati formulation it can be called as Maha Shankha Vati. After studying various reference mentioned in Ras Shastra, Standard operative procedure of Maha Shankha Vati can be classified into two types:- In above two SOP only difference in Shankha Processing, in first SOP Shankha Bhasma is prepared by giving Gaja Puta and in second SOP Shankha Marana has been done by Quenching method.Variations found in Bhavana Dravya, Bhavana Sankhya, Size, Anupana, Grahan Kala of Maha Sankha Vati among all classics. like There are found references about Apamarga Patra Swaras, Apamarga Mula Kwath. In AFI Chitrak Mula & Apamarga Panchanga, mentioned in the form of Kwatha. Bhavana of Amlavarga Dravya must be given upto it becomes Amla in test. To go to details go through this Study which having mentioned all the details.